We Aren't Just 'Slack'ing Off: Utilizing a Digital Tool to Connect Emerging Women Leaders in Global Health. Issue 1 (12th September 2022) - Weinberg, Jennifer L.; El-Harakeh, Amena; Kiplagat, Sandra; Abubakar, Aisha Ahmed; Iyengar, Sloka; Marconi, Agustina M.; Vaghaiwalla, Tanaz M.; Kalbarczyk, Anna; Harrison, Meagan
Background: Investing in women leaders in global health catalyzes growth and positive outcomes for individuals and their communities, yet large gender disparities persist in leadership within the field due to several barriers. The use of digital tools facilitates cross-institutional and international collaborations to allow individuals or groups to create or share information, ideas, career interests, and other forms of expression via virtual communities. Digital tools can dramatically expand access to and the quantity and quality of opportunities for networking, mentoring, and collaboration to support women in their professional development. Objectives: The objective of this paper is to document tangible examples of positive experiences, connections, or collaborations resulting from connecting with other participants in a Slack network. We aimed to evaluate this network to understand how to better build, model, and scale advantageous digital networks of women leaders in global health moving forward. Methods: Semi-structured interviews were conducted virtually with seven members of the Slack network from Africa and North America who volunteered to share their experiences. Transcripts of six of these interviews were analyzed for key points using thematic analysis to derive short vignettes from each interview. Findings: The findings of this study indicate that Slack is a highly beneficial tool for women in global health to use for facilitating job searches, mentoring opportunities, promoting project collaborations, and proposing programming and outreach ideas in a remote environment. We found distinct recommendations for utilizing this digital networking tool in a way that best supports and engages women in global health. It is important to spread awareness and ensure visibility of the network to recruit and maintain members, design the network in a way that inspires internal motivation, encourage consistent and meaningful engagement, send weekly emails, and maintain accessibility for a global membership base. Conclusions: The Slack network provides an engaging digital tool that facilitates communication, opportunities, and growth among women in global health. Digital tools such as Slack can help to increase opportunities for participants from low- and-middle-income countries to engage in the same networking and leadership opportunities as individuals from high-income countries. It remains critical to continue to build, advance, and scale advantageous networks like Slack to promote equity and accessibility among women leaders in the global north and south into the post-pandemic world.